Pengaruh Rebusan Daun Kelor terhadap Produksi ASI Ibu Nifas di Desa Pilar Jaya Tahun 2022 - Siti Hajar; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Aulia Ariyani (Jurnal Siti Rufaidah, 2024)
One of the plants that is believed to help increase breast milk production is the Moringa leaf (Moringa oleifera). This plant is known as the "miracle tree" because of its very complete nutritional content, such as vitamins A, C, E, calcium, iron, and protein. In addition, Moringa leaves also contain phytochemical compounds that function as galactagogues, which are substances that stimulate breast milk production. The purpose of this study was to determine the effect of giving Moringa leaves on the smoothness of breast milk production in postpartum mothers in Pilar Jaya Village, Rusip Antara District, Central Aceh Regency in 2022. The type of research is Quasi-experimental with a quantitative research design, to explain, test the relationship between variables, and to find out whether there is an effect of giving boiled Moringa leaves on the smoothness of breast milk in postpartum mothers in Pilar Jaya Village, Rusip Antara District, Central Aceh Regency. This research was conducted in Pilar Jaya Village, Rusip Antara District, Central Aceh Regency. Central Aceh in 2022. The population in this study was 20 people, then the sample was part of the entire object studied and was considered to represent the entire population. The number of samples used was 20 people using the Simple Total Sampling technique, the results of the study using the Wilcoxon statistical test with a significance level of sig α 0.05 obtained a p-value of 0.000 <0.05 with a Z value of -3.754 which means there is a difference before being given boiled moringa leaves and after being given boiled moringa leaves on the Smoothness of Breast Milk in Postpartum Mothers in Pilar Jaya Village, Rusip Antara District, Central Aceh Regency in 2022.